Recent Trends in Gospel of Thomas Research (1991-2006): Part I, The Historical Jesus and the Synoptic Gospels - Perrin, Nicholas (2007)
This article, the first of a two-part series, reviews research between 1991 and 2006 dealing with the Gospel of Thomas. It focuses on two questions: (1) whether the Coptic sayings collection preserves material going back to the historical Jesus, and (2) whether it is dependent on the synoptic Gospels or attests to an independent line of tradition, relatively uninfluenced by the canonical texts. In connection with the former issue, the article observes that Thomas is little used in contemporary Jesus scholarship and seeks to elucidate reasons for this. As to whether or not the author of Thomas was privy to our synoptic gospels, scholarship has been undergoing an ever-deepening entrenchment of positions. This has not only resulted in a scholarly culture that resists making generalizations regarding Thomas’s origins, but has also provoked new approaches to explicating those origins. The article closes with suggestions for future study.
Keywords: Third Quest; Source Criticism; Historical Jesus; Gospels; Gospel of Thomas; Gnosticism